2013
DOI: 10.1590/s1806-37132013000500011
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive sleep apnea and asthma

Abstract: Symptoms of sleep-disordered breathing, especially obstructive sleep apnea syndrome (OSAS), are common in asthma patients and have been associated with asthma severity. It is known that asthma symptoms tend to be more severe at night and that asthma-related deaths are most likely to occur during the night or early morning. Nocturnal symptoms occur in 60-74% of asthma patients and are markers of inadequate control of the disease. Various pathophysiological mechanisms are related to the worsening of asthma sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 68 publications
(169 reference statements)
0
25
0
2
Order By: Relevance
“…Several publications have discussed the relationship between asthma and OSA. 59 60 61 62 63 Salles et al reported that OSA is prevalent in patients with asthma and is associated with disease severity. Asthma is associated with acute and chronic inflammation that affects the respiratory muscles, including upper airway dilators.…”
Section: Discussionmentioning
confidence: 99%
“…Several publications have discussed the relationship between asthma and OSA. 59 60 61 62 63 Salles et al reported that OSA is prevalent in patients with asthma and is associated with disease severity. Asthma is associated with acute and chronic inflammation that affects the respiratory muscles, including upper airway dilators.…”
Section: Discussionmentioning
confidence: 99%
“…The correlation between OSAS and asthma was first investigated by Hudgel and Shrucard in the late 1970s (33). In asthmatic patients, OSAS contributes to poor asthma control (34) especially in patients who suffer most from nocturnal symptoms (35). It has been hypothesized that OSAS and asthma share most of their pathophysiological mechanisms; both often involve airways obstruction, gastroesophageal reflux, and obesity; moreover snoring could be a worsening factors for both the conditions.…”
Section: Sleep Disorders In Asthmamentioning
confidence: 99%
“…Several authors have reported a relationship between asthma and OSA [8][9][10][11][12][13][14]. The prevalence of OSA is higher among patients with adult asthma; OSA symptoms, which further deteriorate asthma symptoms, are commonly observed in the asthmatic population; thus, treating OSA can improve asthma symptoms [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of OSA is higher among patients with adult asthma; OSA symptoms, which further deteriorate asthma symptoms, are commonly observed in the asthmatic population; thus, treating OSA can improve asthma symptoms [9][10][11][12]. Recent studies have shown that adult patients with asthma have a significantly higher risk of OSA [14,15].…”
Section: Introductionmentioning
confidence: 99%